Recent Advances in Design for Manufacture (DFM) 2000
DOI: 10.1115/imece2000-1052
|View full text |Cite
|
Sign up to set email alerts
|

Design of Hydraulic Motor Spindle for High Speed Machining

Abstract: This paper presents the design of a hydraulic motor driven spindle for the processing of metals and composite materials at high rotational speeds. Existing technologies applicable to spindles and spindle holders under severe operating conditions were reviewed. A conceptual design of the hydraulic spindle system was developed. A strong indication of distinct increase in spindle life and gains in cutting power at higher rotational speeds when compared to the conventional electric motor driven spindles underscore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Since the rigidity of the components that transmit the cutting force between the tool and the workpiece is important in the size of the cutting force, the use of hydraulic spindles helps in reducing this rigidity, which leads to a reduction in force. Agba 2 has reported that using a hydraulic spindle can help reducing vibrations in machining which is also manifested in improved surface roughness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the rigidity of the components that transmit the cutting force between the tool and the workpiece is important in the size of the cutting force, the use of hydraulic spindles helps in reducing this rigidity, which leads to a reduction in force. Agba 2 has reported that using a hydraulic spindle can help reducing vibrations in machining which is also manifested in improved surface roughness.…”
Section: Discussionmentioning
confidence: 99%
“…Another study focused on the use of spindles with water-lubricated hydrostatic bearings. 4 The aim of this study was to 1 Mechanical Engineering Department, Islamic Azad University Najafabad branch, Isfahan, Iran 2 Mechanical Engineering Department, Islamic Azad University Mobarakeh Branch, Iran 3 Mechanical Engineering Department, University of Kashan, Iran improve the machining accuracy in cutting and grinding precision parts. To reduce the radial vibration of the rotor, it is very important to increase the flexural stiffness of the overhang area so that the radial vibration can be completely reduced to an acceptable level for the final cutting operation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation